Differences Between Drill Training and Play Training Methods Towards Badminton Skills - Ashadi Cahyadi; Ade Rahmat (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. This study was to determine the difference between drill and play training methods on badminton playing skills. Materials and methods.The method used is the experimental method. The research subjects were 30 male athletes at the PB Aneka club and had taken the achievement motivation test. The data collection tool in this study used the Playing Badminton test. The hypothesis test anova one way. Results. The results of the research in the high achievement motivation badminton group obtained an F-Count value of 119.61 while the FTable with degrees of freedom 1 (df1) and degrees of freedom 2 (df2) and a significance of 0.05 obtained an FT-table value of 4.20. F-Count > FTable (119.61 > 4.20) and in the low-achieving motivation badminton group, the F-Count value is 4.840 while FTable with degrees of freedom 1 (df1) and degrees of freedom 2 (df2) and a significance of 0.05 obtained FTable value of 4.20. FCount > FTable (4,840 > 4,20) Conclusions.There is a significant difference between the drill and play training method groups on badminton skills on high and low achievement motivation.